Approach and language - Ambrose, Gavin; Aono-Billson, Nigel (Basics graphic design, 2011)
Looks at the initial stages of the design process and the vocabulary used on undergraduate design courses. This book begins with an overview of various approaches to graphic design, as well as its inherent language. It also looks at methods for generating and developing ideas, research methods, and understanding what is meant by the design brief